Islam and Politics: The Basic Propaganda of The Islamic State by Masyumi in Selayar - Rahmatul Yushar; Hasaruddin Hasaruddin; Syamzan Syukur (Pascasarjana UIN Alauddin Makassar, 2023)
The purpose of this study is (i) to describe the struggle of Islam and politics (the basic debate of the state) as an initial analysis, (ii) the basic propaganda of the state based on Islam (the implementation of Islamic teachings and laws in the life of a person, society, state) as the goal of the party. Masyumi, (iii) the basic propaganda of the Islamic state by Masyumi in Selayar. This study uses a qualitative descriptive analytic research. This research focuses on the Selayar area, which became the site of the campaign carried out by Masyumi in 1950. This research uses historical research steps that are generally carried out, starting with Heuristics, Source Criticism, Interpretation, and Historiography. The research uses a religious, social and political theory approach. The results of this study indicate that (i) there are different views among Islamic scholars in responding to political positions in Islam, (ii) Masyumi is an Islamic party that fights for Islam as a foundation in personal, community and state life through the constituent line (iii) Massive propaganda The basis of an Islamic state carried out by Masjumi cadres in Selayar has become a real thing in sharpening its influence to local level politics (Selayar). The implications of this research are expected to be able to provide insight regarding Masyumi's activities in achieving its goals. In addition, this research is expected to be the first step in revealing further the turbulence of thinking about the ideal state basis at that time.